Assessing the effects of deforestation on the livelihoods of local people in Rupandehi District, Nepal - K.C. Laxmi; Tsusaka, Takuji W.; Sasaki, Nophea; Kuwornu, John K.M.; Asian Development Bank - Japan Scholarship Program (ADB-JSP) (Pathum Thani : Asian Institute of Technology, 2019)
While deforestation is recognized to pose threats to humans, there is inadequate research conducted at the local level on its livelihood effects. This study analyzed the effects of deforestation on the livelihoods of local people in Rupandehi district of Nepal by assessing perception of local people towards deforestation, livelihood assets, and the effects of deforestation on five types of livelihood capitals. Data were collected from 156 households, and descriptive statistics, and parametric inferential statistics were used for analysis. Local people perceived encroachment and conversion of forestland to agricultural land having increased in the past 20 years. The indicator of changes in overall livelihood asset on the scale of zero to one, where zero indicates negative changes, 0.5 no change, and one positive changes, was 0.73. The result of seemingly unrelated regression (SUR) analysis showed that deforestation had negative effects on natural, physical, human, and social capital and positive effects on financial capital. It was also found that deforestation negatively affected consumption of fuel wood and fodder. Based on the findings, policies should address each livelihood capital differently, and there is a need for strong implementation of forestry related policies and creation of livelihood promotion programmes with a long-term goal.
A thesis submitted in patial fulfillment of the requirements for the degree of Master of Science in Natural Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2019
Keywords: Forests and forestry -- Nepal -- Rupandehi; Deforestation -- Nepal -- Rupandehi